Laying it on thick: a study in secondary growth - Turley, Emma K; Etchells, J Peter (Journal of experimental botany, 2022)
Abstract The development of secondary vascular tissue enhances the transport capacity and mechanical strength of plant bodies, while contributing a huge proportion of the world’s biomass in the form of wood. Cell divisions in the cambium, which constitutes the vascular meristem, provide progenitors from which conductive xylem and phloem are derived. The cambium is a somewhat unusual stem cell population in two respects, making it an interesting subject for developmental research. Firstly, it arises post-germination, and thus represents a model for understanding stem cell initiation beyond embryogenesis. Secondly, xylem and phloem differentiate on opposing sides of cambial stem cells, making them bifacial in nature. Recent discoveries in Arabidopsis thaliana have provided insight into the molecular mechanisms that regulate the initiation, patterning, and maintenance of the cambium. In this review, the roles of intercellular signalling via mobile transcription factors, peptide–receptor modules, and phytohormones are described. Crosstalk between these regulatory pathways is becoming increasingly apparent, yet the underlying mechanisms are not fully understood. Future study of the interaction between multiple independently identified regulators, as well as the functions of their orthologues in trees, will deepen our understanding of radial growth in plants. We review the literature describing the molecular mechanisms by which the vascular cambium is initiated and maintained in Arabidopsis.